Estilos de aprendizaje de los estudiantes del segundo semestre de Licenciatura en matemáticas - Janz Jaramillo-Benitez; Jaime Rincon-Leal (Ecomatemático, 2019)
The present research aimed to identify the learning styles of second semester students of Mathematics at the Universidad Francisco de Paula Santander. The study is quantitative with a quasi-experimental transectional design of a descriptive type with a sample of 30 students; we used the questionnaire of Habits and Styles of Learning (CHAEA) of Honey -Alonso. It was evidenced that 46.67% of the students have predominance in the reflexive learning style while only 10% are Pragmatic style, in the same way the statistical software SPSS Version 23 was used for the analysis of the information